PENGEMBANGAN PEMBELAJARAN INKUIRI BERBANTUAN MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN IPA KELAS V SD - Ignatius Joko Dewanto; Sholeh Hidayat; Dodi Sukmayadi (LPPM Universitas Muhammadiyah Muara Bungo, 2021)
Inquiry is learning that maximally involves all the abilities of students to find and investigate natural phenomena, living things or objects critically, analytically and logically to produce creative and innovative students in solving problems. The purpose of this study was to produce interactive multimedia assisted inquiry learning in science subjects in grade V elementary schools to improve critical thinking skills. The research method used is research and development of learning approaches by Borg and Gall and the Dick and Carey learning design model. The design used was: R&D, ADDIE, SDLC, Tesmer's formative evaluation model. The contribution of this research is to obtain a standardized interactive multimedia design based on the inquiry learning model which can help teachers implement science learning, for the formation of the students competence of Class V elementary school, implications for increasing teacher productivity and increasing competence in student learning for fifth grade elementary school. The follow-up of this interactive multimedia development research has implications for increasing teacher productivity and increasing competence in learning student for fifth grade elementary school.